ANALISIS KEBUTUHAN IMPLEMENTASI KURIKULUM SEKOLAH PENGGERAK DI SDIT AL-AMIN KAPUAS - Sukaryati Sukaryati; Siminto Siminto (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2022)
This study aims to obtain a map of the implementation needs of the driving school curriculum at SDIT Al-Amin Kapuas. Implementation is an action or implementation of a plan that has been prepared carefully and in detail. Implementation is usually done after planning is considered perfect. The objectives of this research are: (1) To describe the implementation of the driving school curriculum at Al-Amin Kuala Kapuas Integrated Islamic Elementary School, (2) To analyze the supporting and inhibiting factors for implementing the driving school curriculum at Al-Amin Kuala Kapuas Integrated Islamic Elementary School , (3) To analyze and describe the steps taken by the school to minimize the inhibiting factors for the implementation of the driving school curriculum at Al- Amin Kuala Kapuas Integrated Islamic Elementary School. Techniques in data collection namely observation, interviews and documentation. Qualitative data analysis. Data analysis techniques in this study are data reduction, data display, and conclusion drawing/verification. Checking the validity of the data in this study used triangulation techniques. From the description above it can be concluded several things as follows; 1) The steps taken in implementing the curriculum are planning, making goals, making supporting programs, supervising, evaluating success. 2) There are several factors supporting and inhibiting the implementation of the curriculum including 1) Readiness of educators, 2) Readiness of educational staff, 3) Condition of supporting facilities and infrastructure, 4) Readiness of students, 5) Impact of implementation. 3) The need for special steps or handling by the school in overcoming the inhibiting factors of curriculum implementation so that the curriculum implementation is effective.